Influence of metal exposure on metallothionein synthesis and lipid peroxidation in two bivalve mollusks: the oyster (Crassostrea gigas) and the mussel (Mytilus edulis) - Geret, Florence; Jouan, Agnès; Turpin, Vincent; Bebianno, Maria João; Cosson, Richard P. (Aquatic Living Resources, 2002)
The impact of metals (silver, cadmium, copper, mercury and zinc) on metallothionein (MT) and malondialdehyde (MDA) levels of the oyster (Crassostrea gigas) and the mussel (Mytilus edulis) was studied after 4 or 21 days of metal exposure. Moreover, total protein levels were determined. After 4 days of metal exposure, although C. gigas and M. edulis accumulated cadmium and mercury concentrations in the gills and digestive gland, no significant variation of total protein level was occurred. After 21 days of exposure, metals were bioaccumulated in the gills and the digestive gland of both mollusks. A decrease of total protein concentrations in the gills of oysters and the digestive gland of mussels and an increase on metallothionein concentrations in the gills of both mollusks were observed. An increase of MDA levels was noticed for the gills and the digestive gland of mussels exposed for 21 days to either cadmium, silver or mercury whereas a decrease of MDA levels was observed in the gills of the oysters exposed for the same time to the same metals. The levels of proteins, MDA and MT were metal, species or organ dependent. info:eu-repo/semantics/publishedVersion